PLANNING AND DESIGNING OF MODERN MORTUARY COMPLEX IN TERTIARY CARE (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Rapid modernization and exponential sophistication have take place over the last century in the field of medical sciences but a lot is desired for those who dead and need to be laid to rest with peace, dignity and respect. The importance of proper decent facilities and services of modern postmortem complex will play a vital role and Yeoman services to the harassed layman. So that even the most reluctant mortuary visitor would not mind entering the complex. They will dispel the atmosphere of dislike, fear and hatred presently prevailing in majority of the so-called postmortem building in major part of the country.
Keywords: Mortuary Services; sophistication